Pembentukan Struktur Ruang Kompak di Kawasan Banyumanik Kota Semarang - Ilma, Faradina; Rakhmatulloh, Anita Ratnasari (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Limited availability of space in the city center while population number is rapidly increasing causes activity spaces develop in the suburbs. Banyumanik Area is sub-center development of Semarang City which has rapid population growth and developed into new activity centers with the connecting road network that forms the spatial structure. Although new activity and service centers has been established, Banyumanik Area’s residents dependence and number of movements toward city center are still high so indicates that activity centers in this area can’t serve Banyumanik’s residents needs yet. On the other hand, to create sustainable cities that can serve residents needs, Compact City concept has been developed through mixed land use, high density, and efficient public transport. This research aims to analyze compactness characteristics of Banyumanik’s spatial structure, its affecting elements, and its development trend based on experts opinion. This research used positivistic approach with descriptive analysis techniques. The results shows that Banyumanik Area’s spatial structure has not formed compact spaces yet characterized by low density area, mixed land use is growing in a linear form, public transportation has not reach some settlements yet, and dominant used of private vehicles compared to public transport and on foot.